2021
DOI: 10.1097/md.0000000000028184
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of Qingshu Yiqi decoction as a complementary and alternative therapy for COVID-19 with Delta variant

Abstract: Background: Qingshu Yiqi decoction combined with general western medicine are important and prevalent recently treatment method of corona virus disease 2019 (COVID-19) with Delta variant, but the efficacy and safety were not clear. This meta-analysis aims to clarify their clinical efficacy and safety thus to provide evidence for clinical application. Methods: We searched Chinese databases CNKI, Wanfang, VIP and English databases PubMed, Cochrane Library, Embase for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…17 The CAT options for COVID-19 and post-COVID-19 includes homeopathy which targets physical and mental problems, 17 yoga and stress management and lifestyle, 18 ayurveda, 19 herbal medicine, 20,21 green tea, 22 flavonoid, 23 meditation, 24 mindfulness, 25 acupressure and Liu Zi Jue Qigong, 26 acupuncture, 27 cognitive-spiritual hope and Taichi, 28 reflexology, 29 relaxation, 30 psychoeducation and mind-body complementary therapy 31 and Qingshu Yiqi decoction. 32 Although those complementary and alternative therapies mentioned above are promising the success to reduce the symptoms of COVID-19 as well as post COVID-19, varied mechanisms and targeted symptoms are specific considerations to choose STT in this community empowerment with its simplicity, self-guide protocols and flexibility to implement for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 The CAT options for COVID-19 and post-COVID-19 includes homeopathy which targets physical and mental problems, 17 yoga and stress management and lifestyle, 18 ayurveda, 19 herbal medicine, 20,21 green tea, 22 flavonoid, 23 meditation, 24 mindfulness, 25 acupressure and Liu Zi Jue Qigong, 26 acupuncture, 27 cognitive-spiritual hope and Taichi, 28 reflexology, 29 relaxation, 30 psychoeducation and mind-body complementary therapy 31 and Qingshu Yiqi decoction. 32 Although those complementary and alternative therapies mentioned above are promising the success to reduce the symptoms of COVID-19 as well as post COVID-19, varied mechanisms and targeted symptoms are specific considerations to choose STT in this community empowerment with its simplicity, self-guide protocols and flexibility to implement for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Delta variant in 2021 showed that it was the most contagious variant and spread rapidly in unvaccinated individuals [9]. More infectivity, higher viral load, and higher pathogenicity were detected in the Delta variant than in other varials [10,11].…”
Section: Early Onlinementioning
confidence: 99%
“…Qingshu Yiqi Decoction (QSYQD) is a summer-heat clearing formula, which has the effects of clearing summer-heat, reinforcing Qi, nourishing Yin (usually seen as " restorative energy”) and generating fluid ( Xia et al, 2021 ). This herbal remedy contains nine primary components in Table 1 and is usually translated as Decoction for Clearing away Summer-heat and Reinforcing Qi.…”
Section: Herbal Formulas Of Tcm Against Hsmentioning
confidence: 99%